Reach for the stars: The impact on consumer preferences of introducing a new top-tier typology into a PDO wine - Gabriele Scozzafava; Francesca Gerini; Andrea Dominici; Caterina Contini; Leonardo Casini (Wine Economics and Policy, 2018)
In a world characterized by a significant evolution in wine consumption, Protected Designations of Origin (PDO) wines have constituted a valid strategy of marketing and competitiveness for producers. In 2014, the Consorzio Vino Chianti Classico created the "Chianti Classico Gran Selezione" DOCG (Denominazione di Origine Controllata e Garantita) to strengthen and expand the quality range of its productions. This is a new typology of Chianti Classico placed at the top of the quality production pyramid. The aim of this study is to verify whether the introduction of a higher-tier certification within a PDO denomination can represent an effective strategy to leverage brand value and strengthen the relationship between quality production and territory. With this purpose in mind, we performed a choice experiment on Italian wine consumers. A Latent Class Model allowed us to identify three distinct classes of consumers that differ in their preferences for price and PDO. Moreover, we performed a Chi-squared Automatic Interaction Detection technique and a Principal Component Factor Analysis for describing these classes according to consumers' attitudes and personal characteristics. Our results show the existence of a segment that appreciates the introduction of the new label and therefore support the effectiveness of developing this strategy.
Keywords: 330; Chianti; Choice experiment; Market share; PDO wine; Segmentation